A new lawsone azo-dye for optical sensing of Fe3+ and Cu2+ and their DFT study. Issue 18 (16th September 2016) - Sonawane, Mahendra; Tayade, Kundan; Sahoo, Suban K.; Sawant, Chatur P.; Kuwar, Anil
Abstract: A new lawsone-based azo-dye 2-hydroxy-3-((pyridin-2-ylmethyl)diazenyl)naphthalene-1, 4-dione (1 ) was synthesized and applied for sensing of metal ions. Receptor1 showed selective fluorescent and colorimetric response for the detection of Cu 2+ and Fe 3+ over other tested metal ions. The fluorescence intensity of1 was significantly quenched allowing detection of Fe 3+ and Cu 2+ down to 0.61 and 6.06 μM, respectively. The binding has been established by fluorescence spectroscopic method. Receptor1 provided a 1 : 1 binding scaffold for recognition of Fe 3+ and Cu 2+ ions with the association constant of 3.33 × 10 6 and 3.33 × 10 5 M −1, respectively. The B3LYP/6-31G/LANL2DZ method was employed for the optimization of1 and1 ·Fe 3+ and1 ·Cu 2+ . Abstract :